The gender of piety : family, faith, and colonial rule in Matabeleland, Zimbabwe - Urban-Mead, Wendy (Athens, Ohio : Ohio University Press, 2015)
The Gender of Piety is an intimate history of the Brethren in Christ Church in Zimbabwe, or BICC, as related through six individual life histories that extend from the early colonial years through the first decade after independence. Taken together, these six lives show how men and women of the BICC experienced and sequenced their piety in different ways. Women usually remained tied to the church throughout their lives, while men often had a more strained relationship with it. Church doctrine was not always flexible enough to accommodate expected masculine gender roles, particularly male membership in political and economic institutions or participation in important male communal practices. The study is based on more than fifteen years of extensive oral history research supported by archival work in Zimbabwe, the United Kingdom, and the United States. The oral accounts make it clear, official versions to the contrary, that the church was led by spiritually powerful women and that maleness and mission-church notions of piety were often incompatible. The life-history approach illustrates how the tension of gender roles both within and without the church manifested itself in sometimes unexpected ways: for example, how a single family could produce both a legendary woman pastor credited with mediating multiple miracles and a man - her son - who joined the armed wing of the Zimbabwe African People's Union nationalist political party and fought in Zimbabwe's liberation war in the 1970s. Investigating the lives of men and women in equal measure, The Gender of Piety uses a gendered interpretive lens to analyze the complex relationship between the church and broader social change in this region of southern Africa.
The gender of piety in Matabeleland -- Matshuba Ndlovu: masculinity and faith in Matabeleland, 1898/1930 -- Maria Tshuma: chastity and female piety, 1920/70 -- Nakaseyemephi Ngwenya: a church planter Emaguswini, 1950/73 -- Sandey Vundhla: being fruitful for the church, 1950/70 -- Mansimango (Sithembile Nkala): sellouts, comrades, and Christians in the liberation war, 1969/78 -- Stephen N. Ndlovu: gendered piety, the new Zimbabwe, and the Gukurahundi, 1980/89 -- Gendered lives of piety -- Ndlovu and Nsimango family tree.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Brethren in Christ Church -- Zimbabwe -- Matabeleland -- History -- 20th century -- Case studies; Brethren in Christ Church -- Zimbabwe -- Matabeleland -- Biography; Brethren in Christ Church; Sex role -- Religious aspects -- Brethren in Christ Church; Christianity and politics -- Zimbabwe -- Matabeleland -- History -- 20th century; Matabeleland (Zimbabwe) -- Church history -- 20th century; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christianity / Denominations; HISTORY / General; Electronic books